A Study on Listening Difficulties Faced by students - Sri Rumiyatiningsih Luwiti; Irmawaty Umar; Sahrin Mustapa (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
In learning English, one of the most difficult skills for students was listening. There were various causes that make it difficult for students in listening skill. This study was aimed find out the difficulties that faced by students while listening. This study was applied descriptive qualitative method because the data was gaining the information relate listening difficulties and the data was collected from questionnaire as the main instrument. This study was conducted at SMPN Widya Krama, while participants of this study were the students of class 8 grades and the total of participants were 20 students. Based on the result of this study, the students encountered various difficulties such as the quality of recording used in listening, Students’ vocabulary was limited, length and speed of listening, various kinds of accents and cultural differences.